Spin Doctoring in modern political discourse: linguistic aspect - Ковалевська, Анастасія Володимирівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2021)
In the article, the realization of verbal influence (also known as suggestion) phenomenon in political discourse is considered. This concept is defined as a whole combined image of the text itself and emotions of its recipient and addressee,including the peculiarities of perception, external and internal circumstances, its pragmatic and linguistic aspects, etc, and is aimed at a a political subject’s influencing a political object. Usually, political discourse and its immanent influential properties are researched from the standpoint of Psychology, Communicative Linguistics, Pragmalinguistics, Political Linguistics and other related sciences, but the author proposes to involve Neurolinguistic Programming as a modern science which deals with analyzing the peculiarities of perception, processing and generation of information and its transformations from deep thought structures to superficial speech; as well as Spin-Doctoring, an ultramodern complex discipline aimed at correcting the negative image of the event in the media after its has already happened or right before its manifestation, which is impossible without the involvement of language techniques to influence the recipient or a group of them. In order to fully research the political discourse, which in the network of this article is represented by the political speeches of the leaders of Ukraine, USA, France, Spain, Italy, Canada, Germany, the author involves both the basic Spin Doctoring techniques of political discourse correction ( negative information delay, ambiguous informing, focus switch, interspersing the artificial situations with elements of naturalness, and the technique of controlled information leaks and preparation for events expectations); and the NLP paradigm meta- and Milton-model analysis text having been utilized in order to isolate the actual linguistic influential patterns (markers of language metamodel processes, simple, complex and indirect inductions). The analysis details the available information on the peculiarities of implementing and enhancing the linguistic influence within the political discourse, as well as outlines the crucial next steps in the further researches on this topic, especially ones in the field of Ukraine’s state information security, which is a particularly important aspect of the state’s modern information during hybrid wars.